2008
DOI: 10.1002/marc.200800092
|View full text |Cite
|
Sign up to set email alerts
|

Effect of an Organically Modified Nanoclay on Low‐Surface‐Energy Materials of Polybenzoxazine

Abstract: Novel low surface free energy materials of polybenzoxazine/organically modified silicate nanocomposites have been prepared and characterized. The CPC (cetylpyridinium chloride)/clay10%/poly(3‐phenyl‐3,4‐dihydro‐2H‐1,3‐benzoxazine) (PP‐a) material possesses an extremely low surface free energy (12.7 mJ · m−2) after 4 h curing at 200 °C, which is even lower than that of poly(tetrafluoroethylene) (22.0 mJ · m−2) calculated on the basis of the three‐liquid geometric method. X‐Ray photoelectron spectroscopy (XPS) s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(28 citation statements)
references
References 23 publications
0
28
0
Order By: Relevance
“…Transmission electron microscopy (TEM) images of the PBZ/MMT nanocomposites revealed partially exfoliated/intercalated structures. We have also prepared new hybrid materials from cetylpyridinium chloride (CPC), clay, and poly(3‐phenyl‐3,4‐dihydro‐2 H ‐1,3‐benzoxazine) (PP‐a) . These novel low‐surface‐free‐energy materials, PBZ/organically modified silicate nanocomposites, possessed intercalated structures (based on X‐ray analyses) as well as enhanced water contact angles, values of T g and T d , and char yields, compared with those of PP‐a alone, when the clay loading was increased from 3 to 10 wt%.…”
Section: Pbz/silica Nanocompositesmentioning
confidence: 99%
“…Transmission electron microscopy (TEM) images of the PBZ/MMT nanocomposites revealed partially exfoliated/intercalated structures. We have also prepared new hybrid materials from cetylpyridinium chloride (CPC), clay, and poly(3‐phenyl‐3,4‐dihydro‐2 H ‐1,3‐benzoxazine) (PP‐a) . These novel low‐surface‐free‐energy materials, PBZ/organically modified silicate nanocomposites, possessed intercalated structures (based on X‐ray analyses) as well as enhanced water contact angles, values of T g and T d , and char yields, compared with those of PP‐a alone, when the clay loading was increased from 3 to 10 wt%.…”
Section: Pbz/silica Nanocompositesmentioning
confidence: 99%
“…In another study, Fu et al reported cetylpyridinium chloride (CPC)‐modified polybenzoxazine (PP‐a)/clay nanocomposites 79. The structures of monofunctional benzoxazine P‐a and its polymer PP‐a are depicted in Scheme .…”
Section: Preparation and Curing Of Polybenzoxazine‐based Compositesmentioning
confidence: 99%
“…Many papers define nanocomposites as polymer compounds which have a multilateral particle in the nanometer range [1–4]. Several types of polymer/clay nanocomposites have been developed by both academia and industry over the past decade [5–11]. Much of the work in this field has focused on polymer nanocomposites of poly(ethylene terephthalate) (PET) and a layered silicate such as montmorillonite (MMT) due to their commercial viability.…”
Section: Introductionmentioning
confidence: 99%